The depressive disturbances characteristic of forsed migrants during military conditions - Mishyiev Вячеслав; Chumakova Ірина (Psychosomatic Medicine and General Practice, 2025)
The phenomenology of depressive disorders was studied in 96 displaced persons, who were divided into two subgroups with signs of recurrent depressive disorder (RDD; F 33) - 34 people and with signs of adaptation disorder in the form of a prolonged depressive reaction (PDR; F 43.21) - 62 people. A clinical and psychopathological study was conducted using a structured interview and a psychodiagnostic study using the M. Hamilton Depression Rating Scale (HDRS) and the A. T. Beck Depression Inventory (BDI). According to the analysis of complaints in the study groups, it was found that for persons with signs of PDR, complaints of a somatic profile were characteristic: deterioration of appetite, sleep, working capacity and decreased libido. Complaints of an affective orientation were less pronounced: irritation and a feeling of tension. The RDD group was characterized by pronounced complaints of both affective and somatic orientation. According to the psychodiagnostic study, it was found that 81.08% (54 people) of patients with PDR have low depression and 17.57% (7 people) have no depressive symptoms. The group with signs of RDD is characterized by significantly higher rates of depression in 37.5% (14 people) - average rates and 62.5% mild (20 people). In 77.03% with signs of PDR, depressive symptoms are focused on sleep disorders, a feeling of tension, decreased performance, and an unreasonable feeling of anxiety when there is no threat to their mental health. For IDPs with signs of RDD, manifestations of depression are accompanied not only by physiological discomfort and changes in physical condition (inhibition, tension, lack of sleep, decreased libido, general somatic symptoms and somatic anxiety), but also by psychoemotional overload from a sense of guilt with suicidal thoughts as a measure of feelings of guilt and self-blame. According to the results of self-assessment, 51.35% of individuals with RDD note mild manifestations of depressive symptoms, and 14.87% have no discomfort in their emotional state at all, and only 33.78% note manifestations of moderate depression. Whereas, individuals with RDD assess their condition more negatively and 50.00% have complaints of moderate depression and 33.33% have pronounced manifestations of depression. According to the results of the Beck Depression Scale questionnaire, we have a reliable distinction between the categories of complaints that form the plot of depressive symptoms. For the group with PDR, these are somatic manifestations according to self-assessment, and for the group with signs of RDD, these are the affective-cognitive sphere.